Bahasa Inggris - Erlinda Putri; Namira Yolanda; Rahmawati Munir (LPPM Politeknik Aceh Selatan, 2022)
Kalimantan is an island surrounded by tropical rain forests and has hot and humid weather because it is crossed by the equator. The hot and humid weather affects the human working climate in the exchange of air in the room, for example in the laboratory. This study objective was to know the amount of air exchange per hour at the Samarinda Occupational Safety and Health Center. The tools used were the TESTO 425 anemometer, a digital meter, a thermohygrometer, a manometer, and a laptop. The chambers where air changes per hour measured were the main laboratory, weighing chamber, UV-VIS spectrophotometer chamber, and atomic absorption and chromatography spectrophotometer chamber. Based on the results of measurements and data analysis, it can be concluded that the ventilation system of 3 out of 4 laboratory chambers has met the recommendation.